2007
DOI: 10.1148/radiol.2431060625
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Embolization and Autologous CD133+Bone Marrow Stem Cells for Liver Regeneration: Initial Experience

Abstract: In patients with malignant liver lesions, the combination of PVE with CD133(+) BMSC administration substantially increased hepatic regeneration compared with PVE alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 25 publications
5
89
0
4
Order By: Relevance
“…Thus, injected MSC do not contribute to liver regeneration through proliferation, but most likely help to establish a micormilieu supportive for intrinsic proliferation of resident hepatocytes. Results acquired by this experimental study confirm the experiences of Furst and Esch, who have previously shown that cell grafts of bone marrow www.intechopen.com origin (CD133 positive cells) applied after PVE in human surgery can increase the FLRV (Furst, 2007). From the present experimental data, however, it cannot be concluded with certainty that the application of stem cells, including MSC, does not support the growth of liver malignancies to the same extent that it supports liver regeneration.…”
Section: Histology and Immunohistochemistrysupporting
confidence: 66%
“…Thus, injected MSC do not contribute to liver regeneration through proliferation, but most likely help to establish a micormilieu supportive for intrinsic proliferation of resident hepatocytes. Results acquired by this experimental study confirm the experiences of Furst and Esch, who have previously shown that cell grafts of bone marrow www.intechopen.com origin (CD133 positive cells) applied after PVE in human surgery can increase the FLRV (Furst, 2007). From the present experimental data, however, it cannot be concluded with certainty that the application of stem cells, including MSC, does not support the growth of liver malignancies to the same extent that it supports liver regeneration.…”
Section: Histology and Immunohistochemistrysupporting
confidence: 66%
“…En 2007 se publicó un artículo donde se trataron a 6 pacientes con tumor hepático que requirió de hepatectomía derecha y posteriormente se realizó una embolización de la vena porta y se administró células madre de médula ósea (BMSCs) CD133+. Se demostró que la regeneración del tejido hepático estaba incrementado en este grupo frente al control, donde solo se realizaba la embolización de la vena porta (28). En 2008, 9 pacientes con cirrosis alcohólica fueron tratados mediante HSCT tras la expansión in vitro de las células CD34+ y su infusión a través de la arteria hepática.…”
Section: Aplicación De Células Madre En Hepatologíaunclassified
“…En 2007 se publicó un artículo donde se trataron a 6 pacientes con tumor hepático que requirió de hepatectomía derecha y posteriormente se realizó una embolización de la vena porta y se administró células madre de médula ósea (BMSCs) CD133+. Se demostró que la regeneración del tejido hepático estaba incrementado en este grupo frente al control, donde solo se realizaba la embolización de la vena porta (28). En 2008, 9 pacientes con cirrosis alcohólica fueron tratados…”
Section: Aplicación De Células Madre En Hepatologíaunclassified